Negative active material, negative pole piece, lithium ion battery and electronic equipment

By optimizing the morphology and particle size distribution of the negative electrode active material, controlling its specific surface area, and combining carbon and silicon materials, the problems of insufficient cycle life and storage performance of lithium-ion batteries are solved, achieving both long life and efficient storage.

CN119400859APending Publication Date: 2025-02-07ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411569861.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The cycle life and storage performance of existing lithium-ion batteries are insufficient, especially due to the priority of the dynamic performance of graphite materials, resulting in increased surface side reactions, reduced cycle life or fast storage capacity decay.

Method used

By optimizing the morphology and particle size distribution of the negative electrode active material, controlling its specific surface area, thereby controlling the consumption of surfactant lithium, using carbon materials to meet the conditions of K≤1, combined with silicon material, a negative electrode sheet and lithium-ion battery are prepared.

Benefits of technology

It realizes the long cycle life and storage performance of lithium-ion batteries, reduces the electrochemical active area and lithium consumption, and improves the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005120208370000061
    Figure BDA0005120208370000061
  • Figure BDA0005120208370000131
    Figure BDA0005120208370000131
  • Figure BDA0005120208370000141
    Figure BDA0005120208370000141
Patent Text Reader

Abstract

The invention provides a negative active material, a negative pole piece, a lithium ion battery and electronic equipment, the negative active material at least comprises a carbon material, and the carbon material satisfies: K < = 1; k is equal to Sbet / A * Spsd; spsd = 6 * sigma (% w * Dn2) / [sigma (% w * Dn3) * rho]; wherein A is a specific surface area correction empirical coefficient which is 7.6; spsd is an equivalent specific surface area calculated according to the particle size distribution of the carbon material, and the unit is m < 2 > / g; sbet is the actual specific surface area of the carbon material obtained through testing, and the unit is m < 2 > / g; dn and% w are respectively the particle diameter of the carbon material and the number ratio of the corresponding particle diameter, n is an integer of 1-100, and the unit of Dn is [mu] m; rho is the true density of the carbon material, and the unit is g / cm < 3 >. According to the negative electrode active material, the negative electrode pole piece, the lithium ion battery and the electronic equipment provided by the invention, the morphology and particle size distribution of the negative electrode active material can be optimized, the specific surface area of the negative electrode active material can be controlled, and the long cycle life and the storage performance of the lithium ion battery can be considered at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode active material, a negative electrode sheet, a lithium ion battery and an electronic device. Background Art

[0002] Lithium-ion batteries have attracted much attention due to their high energy density, reusability and long life, and are widely used in new energy vehicles and energy storage. At present, in these two fields, the focus is on indicators such as the life, storage and cycle comprehensive capabilities of lithium-ion batteries. How to improve the cycle and storage performance of lithium-ion batteries and achieve their long life is a technical problem that people in this field urgently need to solve.

[0003] The positive electrode of lithium-ion batteries, which are mainly used in the fields of new energy vehicles and energy storage, is made of ternary materials or iron-lithium materials, and the negative electrode is mainly made of carbon materials such as graphite. Therefore, the cycle and storage performance of graphite seriously affect the life of lithium-ion batteries. At present, in order to pursue kinetics and rate performance, graphite materials often lead to problems such as increased surface side reactions, reduced cycle life or rapid storage capacity decay. Summary of the invention

[0004] The present invention proposes a negative electrode active material, a negative electrode plate, a lithium ion battery and an electronic device, which can optimize the morphology and particle size distribution of the negative electrode active material, control the specific surface area of ​​the negative electrode active material, thereby controlling the consumption of surface active lithium, and can simultaneously take into account the long cycle life and storage performance of the lithium ion battery.

[0005] In order to solve the above technical problems, the present invention provides a negative electrode active material, comprising at least a carbon material, wherein the carbon material satisfies:

[0006] K≤1;

[0007] K=S bet / A*S psd ;

[0008] S psd =6*∑(%w*D n 2 ) / [∑(%w*D n 3 )*ρ];

[0009] Among them, A is the empirical coefficient for specific surface area correction, which is 7.6;

[0010] S psd is the equivalent specific surface area calculated based on the particle size distribution of the carbon material, in m 2 / g;

[0011] S betis the actual specific surface area of ​​the carbon material obtained through testing, in m 2 / g;

[0012] D n and %w are the particle diameter of the carbon material and the number ratio of the corresponding particle diameter, n is an integer of 1 to 100, D n The unit is μm;

[0013] ρ is the true density of the carbon material, in g / cm 3 .

[0014] In one embodiment of the present invention, the carbon material is selected from at least one of artificial graphite, natural graphite, modified graphite, mesophase carbon microbeads, soft carbon or hard carbon.

[0015] In one embodiment of the present invention, the carbon material is selected from artificial graphite, natural graphite or modified graphite.

[0016] In one embodiment of the present invention, the negative electrode active material further includes a silicon material, and the silicon material is selected from at least one of pure silicon, silicon-oxygen compounds, or silicon-carbon compounds.

[0017] In one embodiment of the present invention, the mass ratio of the silicon material to the carbon material is 0.1:9.9 to 5:5.

[0018] In one embodiment of the present invention, S bet The value range is 0.5m 2 / g~20m 2 / g.

[0019] The present invention also provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode material layer at least arranged on one side of the negative electrode current collector, wherein the negative electrode material layer comprises the negative electrode active material mentioned above.

[0020] The present invention also provides a lithium-ion battery, characterized in that it comprises the negative electrode sheet described above.

[0021] In one embodiment of the present invention, the lithium-ion battery is a secondary battery.

[0022] The present invention also provides an electronic device, comprising the lithium-ion battery described above.

[0023] In summary, the present invention proposes a negative electrode active material, a negative electrode plate, a lithium ion battery and an electronic device, which can effectively optimize the specific surface area of ​​the active material including carbon in the negative electrode plate, make the particle distribution of the negative electrode active material more reasonable, effectively reduce the electrochemical active area, reduce lithium consumption, prevent the problems of low initial efficiency and high lithium consumption during circulation and storage caused by excessive interfaces between the negative electrode active material and the electrolyte, and improve the life of the lithium ion battery. By optimizing the morphology and particle size distribution of the negative electrode active material, controlling the specific surface area of ​​the negative electrode active material, and thus controlling the consumption of surface active lithium, it is possible to simultaneously take into account the long cycle life and storage performance of the lithium ion battery. DETAILED DESCRIPTION

[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0025] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0026] The technical solution of the present invention is further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a negative electrode active material, the negative electrode active material at least includes a carbon material, and the carbon material satisfies:

[0028] K≤1;

[0029] K=S bet / A*S psd ;

[0030] S psd =6*∑(%w*D n 2 ) / [∑(%w*D n 3 )*ρ];

[0031] Among them, A is the empirical coefficient for specific surface area correction, which is 7.6, S psd The equivalent specific surface area is calculated based on the particle size distribution of carbon materials, in m2 / g,S bet is the actual specific surface area of ​​the carbon material obtained through testing, in m 2 / g,D n and %w are the particle diameter of the carbon material and the number ratio of the corresponding particle diameter, n is an integer from 1 to 100, D n To accumulate particles from small to large in size, when the accumulated number accounts for n% of the total number of particles, it is defined as D n Particle size, D n The unit is μm, and ρ is the true density of the carbon material, in g / cm 3 .

[0032] In one embodiment of the present invention, the carbon material is selected from at least one of artificial graphite, natural graphite, modified graphite, mesophase carbon microspheres, soft carbon or hard carbon, etc. Further, the carbon material is selected from at least one of artificial graphite, natural graphite or modified graphite, etc. For example, mesophase carbon microspheres are obtained by refining from asphalt raw materials by direct polycondensation, emulsification, and suspension methods, and the particle morphology is controlled. Modified graphite can be obtained by methods such as low-temperature calcination, surfactant modification, crushing of green body method or coating modification. In a specific embodiment of the present invention, for example, natural graphite particles are subjected to electromagnetic modification, and natural graphite particles are subjected to particle reshaping to obtain modified graphite. In other embodiments, modified graphite can be obtained by other methods. The artificial graphite, natural graphite, modified graphite, soft carbon, and hard carbon materials are well-known terms in the art, and the materials are conventional materials in the art. The present invention does not specifically limit the above materials and will not be repeated here.

[0033] In one embodiment of the present invention, the carbon material is obtained by, for example, precursor crushing, shaping, grading and heat treatment to obtain a carbon material that meets K≤1. Among them, the precursors of artificial graphite include but are not limited to anthracite, needle coke, petroleum coke, asphalt or soft carbon, and the precursors of hard carbon include but are not limited to resin, polymer or biomass. The precursor is crushed into small particles by mechanical grinding or roller grinding, and then shaped and graded. For example, a mechanical fusion machine is used to perform micro-shaping on the surface of the particles. The shaping time is, for example, 1min to 2min. The wind energy opening of the classifier is controlled to remove large and small particles, and the particle size distribution is regulated. The precursor is sintered by heat treatment to form a negative electrode active material, wherein the sintering temperature of graphite materials is, for example, 2700℃ to 3000℃, and the sintering temperature of carbon materials such as hard carbon is, for example, 1300℃ to 1500℃, and the sintering is carried out, for example, in an atmosphere of nitrogen or argon. After sintering, shaping and grading can be performed again to remove oversized or undersized particles to obtain carbon materials. In one embodiment of the present invention, multiple groups of negative electrode active materials are obtained by adjusting the shaping and grading conditions in sequence, and multiple groups of negative electrode active materials are tested, and negative electrode active materials that meet the conditions are selected to prepare lithium-ion batteries. For example, by shaping, the edges and corners of the particle surface are reduced, the sphericity, particle size and quantity of the particles are adjusted, and then the specific surface area of ​​the particles as a whole is controlled, the electrochemical active area is reduced, and the lithium consumption is reduced. And by grading, the particle distribution is reasonable to prevent excessive fine powder, which can reduce the specific surface area, prevent the low initial efficiency caused by excessive interfaces between the negative electrode active material and the electrolyte, and cause large lithium consumption during circulation and storage, thereby improving the life of the lithium-ion battery. Therefore, by adjusting the particle size distribution and morphology of the carbon material, the specific surface area is adjusted to prepare a lithium-ion battery with a long life and low lithium consumption. The processing technology of the above-mentioned specific particle size material is a conventional technical means in the field, which will not be repeated here.

[0034] In one embodiment of the present invention, the particle size distribution of the carbon material is obtained, for example, by a laser particle size analyzer. Specifically, for example, 0.1 g of the carbon material is ultrasonically dispersed in 500 ml of water, and then 20 ml of a dispersant is added, such as nonylphenol polyoxyethylene ether (Np-40), etc. The carbon material is uniformly dispersed by external ultrasound to obtain a test liquid. The test liquid is tested using a Malvern MS3000 device, and the test liquid is poured into a measuring vessel, and the amount introduced is, for example, 5% to 15% of the volume of the measuring vessel. The Malvern MS3000 device is turned on, and the internal ultrasonic intensity of the device is, for example, 100%, and the test time of a sample is, for example, 5 minutes. Other test parameters of the device are shown in Table 1.

[0035] Table 1. Parameters of particle size distribution of carbon materials tested by Malvern MS3000 equipment

[0036]

[0037] In one embodiment of the present invention, the test method in the national standard GB / T 24533-2019 is adopted to take an appropriate amount of carbon material sample and use the true density meter Ultrapyc 1200e to test to obtain the true density ρ of the sample. The specific surface area S of the carbon material bet For example, it can be obtained by nitrogen adsorption test, for example, using a physical adsorption instrument, such as the model of Micromeritics 3030, taking an appropriate amount of graphite sample and placing it in a 9mm ball sample tube, degassing at 300°C for 2h, using nitrogen as the adsorbent, wherein the relative pressure (P / P0) range is, for example, 0.05 to 0.3, and a point is selected every 0.05 to measure the sample adsorption amount to obtain the sample specific surface area S bet .

[0038] In one embodiment of the present invention, when testing the particle size distribution of the carbon material, the test range is set to, for example, 0.01 μm to 3500 μm to ensure the accuracy of the test. In this embodiment, the particle size distribution range of the carbon material is, for example, 0.5 μm to 35 μm. The carbon material is shaped to adjust the particle size and morphology (such as sphericity). The equivalent specific surface area S of the carbon material is psd Can be achieved through: S psd =6*∑(%w*D n 2 ) / [∑(%w*D n 3 )*ρ] to obtain, D n and %w are the particle diameter of the carbon material and the number ratio of the corresponding particle diameter, n is an integer from 1 to 100, D n The unit is μm. The specific surface area correction empirical coefficient A is obtained by fitting, and after correction by A=7.6, K=S is calculated. bet / A*S psd , the carbon material negative electrode satisfying K≤1 has excellent low lithium consumption and long life performance, and the smaller the K value, the better the performance. In a specific embodiment of the present invention, the equivalent specific surface area S of the carbon material psd For example, 0.19m 2 / g~0.4m 2 / g, specific surface area S bet For example, 0.5m 2 / g~20m 2 / g. When the carbon material is a graphite material, the specific surface area S bet For example, 0.5m 2 / g~3m 2 / g, when the carbon material is hard carbon or other carbon materials, the specific surface area S bet For example, 0.5m 2 / g~20m 2 / g. Through shaping and classification, the morphology and particle size distribution of carbon materials are controlled, thereby controlling the equivalent specific surface area S of carbon materials. psd and specific surface area S bet .

[0039] In one embodiment of the present invention, the negative electrode active material also includes a silicon material, which is selected from at least one of pure silicon, silicon oxide compounds or silicon carbon compounds, and the mass ratio of the silicon material to the carbon material is, for example, 0.1:9.9 to 5:5, so as to improve the energy density and stability of the lithium-ion battery.

[0040] In one embodiment of the present invention, a negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode material layer at least arranged on one side of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material, a binder, a conductive agent and a thickener, etc., and the negative electrode active material comprises the above-mentioned negative electrode active material. The negative electrode current collector is, for example, selected from one of a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector or a stainless steel current collector. The negative electrode active material is selected from the above-mentioned negative electrode active materials. The adhesive is, for example, selected from any one or more of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene (Polyhexafluoropropylene) or styrene butadiene rubber (SBR). The conductive agent is, for example, selected from any one or more of conductive carbon black (Super P, SP), acetylene black, carbon nanotubes or graphene, and the thickener is, for example, selected from sodium carboxymethyl cellulose.

[0041] In one embodiment of the present invention, the negative electrode current collector is selected from, for example, a copper foil current collector, and the thickness is, for example, 8 μm to 16 μm. The negative electrode active material is selected from, for example, graphite. The conductive agent is selected from, for example, conductive carbon black. The binder is selected from, for example, styrene-butadiene rubber. The thickener is selected from, for example, sodium carboxymethyl cellulose. Graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of (90-100): (1-5): 1: 2, deionized water is added, and the negative electrode slurry is obtained by stirring. The negative electrode slurry is evenly coated on the copper foil, and after drying at room temperature, the copper foil is placed in a vacuum drying oven, for example, and dried at 120°C for 10 minutes. The dried copper foil is then cold pressed and cut to form a negative electrode sheet.

[0042] The present invention also provides a lithium-ion battery, which includes a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. The separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte is filled between the positive electrode sheet, the separator, and the negative electrode sheet. The negative electrode sheet is selected from the above-mentioned negative electrode sheets. Among them, the lithium-ion battery is, for example, a primary battery or a secondary battery, and more specifically, a secondary battery. The secondary battery is, for example, a soft-pack battery, a hard-shell battery, or a cylindrical battery, etc.

[0043] In an embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed at least on one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The surface of the positive electrode current collector is smooth, and fine纹路 can also be formed on the surface of the positive electrode current collector to improve the adhesion between the positive electrode material layer and the positive electrode current collector. In addition to the foil, the positive electrode current collector can also be used in any one or a combination of multiple forms such as film-like, net-like, porous, foam, or non-woven fabric.

[0044] In an embodiment of the present invention, the positive electrode material layer includes a positive electrode active material, a lithium supplement agent, a binder, and a conductive agent, etc. The positive electrode active material is, for example, selected from at least one of lithium iron phosphate (LiFePO4, LFP) or lithium manganese iron phosphate (LiFe a Mn 1-a PO4, 0.1 < a ≤ 0.5, LMFP), etc., to improve the stability of the positive electrode sheet and the energy density of the lithium-ion battery. The binder is, for example, selected from any one or a combination of polyvinylidene fluoride, polyamide, polyacrylonitrile, polyacrylate, polyethylene ether, polymethyl methacrylate, ethylene-propylene-diene terpolymer, polyhexafluoropropylene, or styrene-butadiene rubber. The conductive agent is, for example, selected from any one or a combination of conductive carbon black, acetylene black, carbon nanotubes, or graphene.

[0045] In an embodiment of the present invention, the positive electrode current collector is, for example, selected from aluminum foil, and the thickness is, for example, 8μm - 16μm. The positive electrode active material is lithium iron phosphate, the binder is, for example, selected from polyvinylidene fluoride, and the conductive agent is, for example, selected from conductive carbon black and carbon nanotubes. In an embodiment of the present invention, after mixing the positive electrode active material, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride, for example, in a mass ratio of (90 - 100):2:1:3, an organic solvent is added and stirred until the system becomes homogeneous to obtain a positive electrode slurry. Among them, the organic solvent is, for example, selected from N-methylpyrrolidone (NMP). The positive electrode slurry is uniformly coated on the aluminum foil, and after drying at room temperature, the aluminum foil is, for example, placed in a vacuum drying oven and dried at 120°C for 10h. Then, the dried aluminum foil is cold-pressed and slit, etc., to make a positive electrode sheet.

[0046] In one embodiment of the present invention, the electrolyte includes, for example, an organic solvent and a lithium salt. The organic solvent is selected from any one or more of battery-grade ethylene carbonate (EC), propylene carbonate (PC), ethyl acetate (EA), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or diethyl carbonate (DEC). The lithium salt is selected from any one or more of lithium bis(fluorosulfonyl)imide (LiFSi), lithium difluorophosphate (LiPO2F2), lithium hexafluorophosphate (LiPF6) or lithium tetrafluoroborate (LiBF4). In one embodiment of the present invention, the lithium salt is selected from lithium hexafluorophosphate, for example, and the organic solvent is selected from a mixture of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate. Ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate are mixed, for example, in a volume ratio of 1:1:1:1, and in an argon atmosphere glove box with a water content of less than 10 ppm, fully dried LiPF6 is dissolved in the mixed organic solvent, and the mixture is mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 is, for example, 1 mol / L.

[0047] In one embodiment of the present invention, the diaphragm is, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film or a polyethylene film, and the thickness of the diaphragm is, for example, 9 μm to 15 μm. In one embodiment of the present invention, the diaphragm is, for example, a polyethylene of 8 μm to 10 μm as a base film, and a nano-aluminum oxide coating with a thickness of 2 μm to 4 μm is coated on at least one side of the base film.

[0048] In one embodiment of the present invention, the positive electrode sheet, the separator, and the negative electrode sheet are stacked in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, the sheet is wrapped with an aluminum plastic film, transferred to a vacuum oven for drying at 120°C, and the prepared electrolyte is injected and sealed, and the electrolyte is formed, and finally a soft-pack lithium-ion battery with a capacity of 1Ah is prepared.

[0049] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0050] Example 1

[0051] Preparation of positive electrode sheet: LiFePO4, conductive carbon black, carbon nanotubes and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 94:2:1:3, and solvent N-methylpyrrolidone was added and stirred until uniform and transparent to obtain positive electrode slurry. The positive electrode slurry was evenly coated on a 16μm aluminum foil, and then the current collector was dried at room temperature and transferred to a vacuum drying oven, dried at 120°C for 10h, and then cold pressed and cut to obtain positive electrode sheets.

[0052] Preparation of negative electrode sheet:

[0053] Graphite preparation:

[0054] Step 1: Precursor crushing: The precursors of carbon-based negative electrode materials, needle coke and petroleum coke, are crushed by mechanical grinding to obtain D V 50 refers to particles of about 10um.

[0055] Step 2: Shaping and grading: Use a mechanical fusion machine to fine-tune the surface of the particles for 2 minutes (parameters: main machine frequency 30Hz, auxiliary machine frequency 60Hz, fan frequency 30Hz, feed frequency 65Hz), then adjust the classifier (feed frequency 20Hz) for regulation, and the obtained particles D V 50 is about 10μm.

[0056] Step 3: Heat treatment: The shaped and graded precursor is sintered by heat treatment (temperature 2700° C.) to form graphite powder.

[0057] Step 4: reshaping and grading: use a mechanical fusion machine to fine-tune the particle surface for 2 minutes (parameters: main machine frequency 30Hz, auxiliary machine frequency 60Hz, fan frequency 30Hz, feed frequency 65Hz); then adjust the classifier (feed frequency 20Hz) to remove oversized or undersized particles to obtain graphite negative active material.

[0058] Negative electrode sheet preparation:

[0059] The prepared graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 95:2:1:2, deionized water is added, and the mixture is stirred thoroughly to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on a 16 μm copper foil, dried at room temperature, and then placed in a vacuum drying oven and dried at 120° C. for 10 minutes. The dried copper foil is then cold pressed and cut to form a negative electrode sheet. The particle size distribution, true density, specific surface area and K value of the graphite are shown in Table 2-3.

[0060] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate, diethyl carbonate and propylene carbonate are mixed, for example, in a volume ratio of 1:1:1:1, and in an argon atmosphere glove box with a water content of less than 10 ppm, fully dried LiPF6 is dissolved in a mixed organic solvent, and the mixture is mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 is, for example, 1 mol / L.

[0061] Selection of separator: 9 μm polyethylene was selected as the base membrane, and a nano-aluminum oxide coating with a thickness of 2 μm was coated on both sides of the base membrane.

[0062] Preparation of battery: The positive electrode sheet, separator and negative electrode sheet are stacked in sequence, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, the sheet is wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, sealed after injecting electrolyte, and the electrolyte is formed, and finally a soft-pack lithium-ion battery with a capacity of 1Ah is prepared.

[0063] In the present invention, different graphite negative electrode active materials are used to prepare lithium ion batteries in Examples 1-6 and Comparative Examples 1-3, wherein shaping conditions and grading conditions are adjusted to obtain multiple groups of graphite negative electrode active materials, the particle size distribution, specific surface area and true density of the multiple groups of graphite negative electrode active materials are measured, and graphite negative electrode active materials with different K values ​​are selected to prepare lithium ion batteries. In different embodiments and comparative examples, the characteristics of the graphite negative electrode active materials are shown in Table 3.

[0064] Table 2. Particle size distribution data of graphite negative electrode active material in Example 1

[0065]

[0066] Table 3. Characteristics of graphite negative electrode active materials in Examples 1-6 and Comparative Examples 1-3

[0067]

[0068] It should be noted that the particle size and morphology of graphite particles can be adjusted by mechanical grinding, shaping and grading or screening. This method is a prior art. Those skilled in the art can adjust the process parameters according to the needs to obtain the desired material, which will not be repeated here.

[0069] In the present invention, different negative electrode active materials are used in Examples 1-6 and Comparative Examples 1-3 to prepare lithium ion batteries, and the performance of the lithium ion batteries is tested. The test results are shown in Table 4.

[0070] Before the test, the new battery is activated by charging and discharging it for 3 cycles at a constant current rate of 0.1C in the test voltage range of 2.5V (discharge cut-off voltage) to 3.65V (charge cut-off voltage), and then tested.

[0071] Test scheme 1 of the present invention:

[0072] The capacity cycle retention rate test is to charge to 3.65V at a constant current of 0.5C under a constant temperature of 45℃, then charge to a cut-off current of 0.05C at a constant voltage; then discharge to 2.5V at a constant current of 1C, which is one cycle, and the discharge capacity of the first cycle is recorded as C1. This process is repeated for 1000 cycles, and the discharge capacity of the 1000th cycle is recorded as C 1000 , C 1000 / C1×100% is the 1000cls cycle retention rate.

[0073] Test scheme 2 of the present invention:

[0074] The high temperature storage capacity recovery rate test is to charge to 3.65V at a constant current rate of 0.33C at a constant temperature environment of 25℃, then charge to a cut-off current of 0.05C at a constant voltage, and then discharge to 2.5V at a constant current rate of 0.33C, and record the initial battery capacity C0. Then charge to 3.65V at a constant current rate of 0.33C, and then charge to a cut-off current of 0.05C at a constant voltage, and place in a 60℃ oven. After 90 days (90d) of storage, take it out, discharge to 2.5V, then charge to 3.65V at a constant current rate of 0.33C, and then charge to a cut-off current of 0.05C at a constant voltage, and then discharge to 2.5V at a constant current rate of 0.33C, and record the battery capacity C2, and record C2 / C0×100% as the storage recovery rate of 90d.

[0075] Table 4 Performance test results of lithium ion batteries in Examples 1-6 and Comparative Examples 1-3

[0076]

[0077] Please refer to Table 3 and Table 4. Comparison of Examples 1-6 and Comparative Examples 1-3 shows that when K≤1, the lithium-ion battery has a good capacity cycle retention rate and high-temperature storage capacity recovery rate. When K>1, the capacity cycle retention rate and high-temperature storage capacity recovery rate of the lithium-ion battery deteriorate, that is, by controlling the particle size distribution of the carbon material in the negative electrode active material, the specific surface area of ​​the particles is controlled, and thus the surface active lithium consumption is controlled, and a carbon material negative electrode and lithium-ion battery with both long cycle life and excellent storage performance are obtained. Comparison of Examples 1-6 shows that as the K value gradually increases, the cycle retention rate and storage recovery rate of the lithium-ion battery gradually deteriorate, that is, the smaller the K value, the better the cycle and storage performance of the lithium-ion battery.

[0078] Please refer to Table 3 and Table 4, D n 50 is the particle size corresponding to the cumulative number fraction of particles in the number base distribution reaching 50%. n 50 are the same, but the K values ​​in Example 4 and Comparative Example 2 are different, and the particle size distribution of the graphite negative electrode active material is different. Among them, the K value of Example 4 is less than 1, and the K value of Comparative Example 2 is greater than 1. The battery cycle and storage performance corresponding to the material of Example 4 are significantly better than those of Comparative Example 2. By comparing Examples 1-6 with Examples 1-3, it can be seen that the K value and D n There is no single strong correlation between K and 50, which is mainly related to the overall particle size distribution of the carbon material. Therefore, when selecting carbon materials, it is necessary to refer to the overall particle distribution morphology of the carbon material to ensure that the K value is not greater than 1, thereby improving the performance of lithium-ion batteries.

[0079] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0080] In summary, the present invention proposes a negative electrode active material, a negative electrode plate, a lithium ion battery and an electronic device, which controls the specific surface area of ​​the negative electrode material including carbon material, thereby controlling the particle morphology (including particle size, sphericity, quantity, etc.) of the negative electrode material, so that the particle distribution of the negative electrode active material is reasonable to improve the performance of the battery, such as preventing the low initial efficiency and high lithium consumption during the cycle and storage process caused by too many interfaces between the negative electrode active material and the electrolyte, thereby improving the life of the lithium ion battery. By optimizing the morphology and particle size distribution of the negative electrode active material, controlling the specific surface area of ​​the negative electrode active material, and thus controlling the consumption of surface active lithium, it is possible to simultaneously take into account the long cycle life and storage performance of the lithium ion battery.

[0081] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0082] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A negative electrode active material, characterized in that: At least comprising a carbon material, wherein the carbon material satisfies: K≤1; K=S bet / A*S psd ; S psd =6*∑(%w*D n 2 ) / [∑(%w*D n 3 )*ρ]; Among them, A is the empirical coefficient for specific surface area correction, which is 7.6; S psd is the equivalent specific surface area calculated based on the particle size distribution of the carbon material, in m 2 / g; S bet is the actual specific surface area of ​​the carbon material obtained through testing, in m 2 / g; D n and %w are the particle diameter of the carbon material and the number ratio of the corresponding particle diameter, n is an integer of 1 to 100, D n The unit is μm; ρ is the true density of the carbon material, in g / cm 3 .

2. The negative electrode active material according to claim 1, characterized in that The carbon material is selected from at least one of artificial graphite, natural graphite, modified graphite, mesophase carbon microspheres, soft carbon or hard carbon.

3. The negative electrode active material according to claim 1, characterized in that The carbon material is selected from artificial graphite, natural graphite or modified graphite.

4. The negative electrode active material according to claim 1, characterized in that The negative electrode active material further comprises a silicon material, and the silicon material is selected from at least one of pure silicon, a silicon-oxygen compound or a silicon-carbon compound.

5. The negative electrode active material according to claim 4, characterized in that The mass ratio of the silicon material to the carbon material is 0.1:9.9 to 5:

5.

6. The negative electrode active material according to claim 1, characterized in that S bet The value range is 0.5m 2 / g~20m 2 / g.

7. A negative electrode plate, characterized in that: The invention comprises a negative electrode current collector and a negative electrode material layer at least arranged on one side of the negative electrode current collector, wherein the negative electrode material layer comprises the negative electrode active material according to any one of claims 1 to 6.

8. A lithium ion battery, characterized in that: Including the negative electrode sheet as described in claim 7.

9. The lithium-ion battery according to claim 8, characterized in that: The lithium ion battery is a secondary battery.

10. An electronic device, characterized in that: A lithium-ion battery comprising any one of claims 8 to 9.